Compendium of key human rights documents of the African Union - Fifth Edition - Magnus Killander (Pretoria University Law Press (PULP), 2013)
Compendium of key human rights documents of the African Union - Fifth Edition Edited by Christof Heyns and Magnus Killander 2013 ISBN: 978-1-920538-16-3 Pages: 513 Print version: Available Electronic version: Free PDF available